1988
DOI: 10.1002/jemt.1060080209
|View full text |Cite
|
Sign up to set email alerts
|

A study of section wrinkling on single‐hole coated grids using TEM and SEM

Abstract: To prevent section wrinkles usually encountered with the use of coated single-hole grids, a simple method was developed. Formvar film resting on a platform with holes (3.5 mm diameter) was heated with a slide warmer (60-65 degrees C). The bottom of a glass petri dish was inverted over the platform to keep the ambient air at the desired temperature. Sections were picked up from the boat of the diamond knife with a single-hole grid and deposited at the orifice of the platform and allowed to dry. The grids were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Sections were again rinsed in blocking buffer (1 2 5 min, 1 2 10 min), TBS-PEG (2 2 10 min), deionized, double-distilled water (2 2 5 min) and then fixed with buffered 8% glutaraldehyde for 10 min. Following rinses in deionized, double-distilled water the grids were transferred and allowed to dry down onto a Formvar support film atop a perforated aluminium platform at 60 8 C overnight (Abad, 1988). Grids were then carefully removed from the platform, inverted (i.e.…”
Section: Immunoelectron Microscopymentioning
confidence: 99%
“…Sections were again rinsed in blocking buffer (1 2 5 min, 1 2 10 min), TBS-PEG (2 2 10 min), deionized, double-distilled water (2 2 5 min) and then fixed with buffered 8% glutaraldehyde for 10 min. Following rinses in deionized, double-distilled water the grids were transferred and allowed to dry down onto a Formvar support film atop a perforated aluminium platform at 60 8 C overnight (Abad, 1988). Grids were then carefully removed from the platform, inverted (i.e.…”
Section: Immunoelectron Microscopymentioning
confidence: 99%
“…One simply has to choose which process works best for them, or devise their own strategy. 1 Gay and Anderson (1954) ; 2 Westfall and Healy (1962) ; 3 Fahrenbach Wolf (1984) ; 4 Galey and Nilsson (1966) ; 5 Mironov et al (2008) ; 6 Anderson and Brenner (1971) ; 7 Rowley and Moran (1975) ; 8 Abad (1988) ; 9 Wells (1974) ; 10 Mironov et al (2008) ; 11 Stevens et al (1980) ; 12 Hall (1995) ; 13 Schalek et al (2012) ; 14 Micheva and Smith (2007) ; 15 Burel et al (2018) ; 16 Leica Microsystems, Germany.…”
Section: Step-by-step Description Of Methods and Considerationsmentioning
confidence: 99%
“…Mesh grids, however, are cumbersome in comparison to single-hole grids owing to the interruption of the field of view by the support bars. Ultrathin acrylic sections mounted on single-hole grids are usually stabilized by application of a formvar support film (Abad 1988). In preliminary studies, we showed that the application of formvar coating was unsuitable for grids exposed to hot solutions because of wrinkling and ultimate failure of the film.…”
mentioning
confidence: 99%